Unusual presentation of trigeminal post-herpetic neuralgia as Hemicrania Continua: A case study - Tiwari, Ashutosh; Shah, Bishal; Manchanda, Rajat; Dhar, Nikita (Nepal Journal of Neuroscience, 2023)
Introduction: Cranial post-herpetic neuralgia sometime becomes refractory to medications. Before increasing the medications detailed history of headache phenotype is very important. Case report: A 41-year-old male developed a herpes infection in the right side first division of the trigeminal nerve two years back before presenting to us. He complained of continuous background dull aching headache (VAS 3 to 4) in the right orbito-fronto-temporal region. Besides this he used to experience sharp shooting severe pain (VAS 8 to 9) for one to two hours, occurring two to three times a day every five to six days for the last two years in same distribution. Episodes of exacerbation were associated with cranial autonomic symptoms (CAS), including right-side eye redness, lacrimation, and nasal congestion. His examination revealed nothing additional than allodynia in the same distribution. His MRI brain revealed no significant abnormality. Different medications were tried but in vain. He was started on Indomethacin to which he responded dramatically. Discussion: Non responsive cases of PHN form a refractory group and might be subjected to unnecessary medications or interventions. Secondary hemicrania continua have been reported due to different causes other than herpes. So, after ruling out secondary causes indomethacin challenge should be the next step in the diagnostic workup.